2018
DOI: 10.1002/cam4.1453
|View full text |Cite
|
Sign up to set email alerts
|

A functional haplotype of NFKB1 influence susceptibility to oral cancer: a population‐based and in vitro study

Abstract: Genetic variations of NF‐κB and its inhibitor IκB genes and their biological mechanism in oral cancer were not well recognized. The purpose of this study was to evaluate the associations of polymorphisms in NFKB1 and NFKBIA with oral cancer susceptibility, and further explore their potential mechanism in vitro. First, the polymorphisms of NFKB1 and NFKBIA were genotyped through iPLEX Sequenom MassARRAY platform in a case–control study with 425 oral cancer patients and 485 healthy controls. Then, the function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…This study showed that the *2*2 homozygous genotype (del/del) was associated with a 2 -fold increased risk (p = 0.041) and with the *2 allele was 1.36 increased risk (p = 0.046). This finding is consistent with a previous report that this polymorphism was not only associated with the risk of oral cancer (Chen et al, 2018b), but also with the development of gastric cancer and colorectal cancer (Cavalcante et al, 2017). GSTM1, one of the glutathione-S-transferase gene family, produces the GSTM1 enzyme involved in the detoxification of polycyclic aromatic hydrocarbons and other carcinogens (Strange and Fryer, 1999).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that the *2*2 homozygous genotype (del/del) was associated with a 2 -fold increased risk (p = 0.041) and with the *2 allele was 1.36 increased risk (p = 0.046). This finding is consistent with a previous report that this polymorphism was not only associated with the risk of oral cancer (Chen et al, 2018b), but also with the development of gastric cancer and colorectal cancer (Cavalcante et al, 2017). GSTM1, one of the glutathione-S-transferase gene family, produces the GSTM1 enzyme involved in the detoxification of polycyclic aromatic hydrocarbons and other carcinogens (Strange and Fryer, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…The group of detoxification genes (GSTM1 and GSTT1) and an inflammatory gene (NF-κB1) are related to tumor-promoting inflammation, while the growth factor genes (TGFβ2 and VEGF) are related to inducing angiogenesis and sustaining proliferative signaling. The (Chen et al, 2018b;Zhou et al, 2009), and several genetic variations are associated with the risk of oral, esophageal, gastric, and colorectal cancers (Lo et al, 2009;Umar et al, 2013;Song et al, 2013;Chen et al, 2018b). The 4-bp ATTG deletion in the promoter of NF-κB1 rs28362491 resulted in the loss of binding to nuclear proteins that reduced promotor activity, hence decreased NF-κB1transcription, and protein production (Karban et al, 2004;Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nine case-control studies from eight included articles [25, 29–35] were correlated with rs28362491 polymorphism. Among the eight studies, four studies [25, 30, 34, 35] were related to rs2233406 polymorphism. Overall, the meta-analysis included three OC articles, three nasopharyngeal carcinoma (NC) articles, and two HNC articles.…”
Section: Resultsmentioning
confidence: 99%
“…They also found that the I allele promoter had significantly higher activity than the D allele and homozygous II genotype cells had higher p50 expression levels than homozygous DD genotype cells. Moreover, Chen F [23] reported that the -94delATTG allele promoter of NFKB1 abolished the binding site of transcription factor and it may increase the susceptibility to oral cancer.…”
Section: Discussionmentioning
confidence: 99%